A Simple Method to Quantify the ex-ante Effects of 'Deep' Trade Liberalization and 'Hard' Trade Protection - Larch, Mario; Tan, Shawn W.; Yotov, Yoto V. (World Bank, Washington, DC, 2021)
This paper proposes a simple and flexible econometric approach to quantify ex-ante the “deep” impact of trade liberalization and the “hard” effects of protection with the empirical structural gravity model. Specifically, the paper argues that the difference between the estimates of border indicator variables for affected and non-affected countries can be used as a comprehensive measure of the change in bilateral trade costs in response to a hypothetical policy change. To demonstrate the effectiveness of these methods, the paper focus on the integration between the countries from the Central European Free Trade Agreement (CEFTA) and the European Union (EU), which is an important policy application that has not been studied before due to lack of data. This analysis overcomes this challenge by utilizing a new dataset on trade and production that covers all EU countries and all CEFTA members (except for Kosovo). The partial equilibrium estimates that we obtain confirm the validity of our methods, while the corresponding general equilibrium effects point to significant and heterogeneous potential gains for the CEFTA countries from joining the EU. The proposed methods can also be extended to ex-post analysis and are readily applicable to other applications, for example, “hard” Brexit.